Modelling impacts of climate variability and land use change on water balance in the Hadejia River Basin, Northern Nigeria - Abba, Umar Da'u (2019)
Hadejia River Basin (HRB) is located in the semi-arid region of northern Nigeria. The total area of the basin is about 24,896 km2 with about 60% of the population engaged in agricultural activities. Other socioeconomic activities are fishing, grazing, and recreation. Almost all the operational activities are climate dependent and sensitive, therefore any change/variation in climate or factors that may aggravate its impacts such as land use change in the basin might have consequential impacts on the water balance and socioeconomic lives of the people of the area estimated at about 15 million inhabitants. This river basin has attracted several studies, however, none of these studies investigated the impact of climate variability and land use change on the water balance of the basin using any hydrological model such as SWAT. Modelling the impacts of future climate and land use change on water balance in the Hadejia River Basin (HRB) was achieved through the following objectives; (i) examining the trends of precipitation and temperature under the recent climate change (ii) determining the presence of trends and variations in the river discharge (iii) predicting the pattern of land use changes based on the past few decades, and (iv) evaluating current and project the impacts of climate variability and land use change on the water balance of HRB. The methods and techniques used to achieve the stated objectives include multivariate statistical analysis such as ANOVA, cluster analysis, multiple linear regression, Mann-Kendall (MK) and Modified Mann-Kendall (MMK) both of which were used for trend and variations analysis. Others were remote sensing, GIS, CA– Markov model for land use change classification, simulation, and prediction. Furthermore, the future impact of climate and land use/cover changes were evaluated using an integrated approach, combining the climate (GCMs), hydrological (SWAT) and the land use prediction (CA–Markov) models. The results showed increased warming with noticeable moisture improvement that is relatively uniform over the entire landscape (1980-2015). Land use analysis indicates a drastic transformation of forest to non-forest land uses, with the construction land uses being the most expanding land use type with percentage changes of 0.50%, 1.95%, 5.31% in 1990, 2000 and 2016 and 7.8% for the projected period (2032). The calibration and validation of the SWAT result was both acceptable with Nash-Sutcliffe (NS) = 0.72 and 0.63, indicating good performance and robustness of the model. For the future simulations (2020-2040) executed in two different scenarios (1st and 2nd). The results show a decline in average annual precipitation (23.4%), runoff (2.1%), baseflow (3.7%), streamflow (20.4%) and potential evapotranspiration (PET) (0.82%) in the first scenario. While, in the second scenario surface runoff rise by 12.6% but yet water yield declined by 27.2%, suggesting the influence of land use change on surface runoff. On the whole, the basin shows a high sensitivity to climate variations than to the changing land use. Despite this reality, attention should be given to climate and land use issues/problems in the basin, before it gets out of hand. Immediate action should be taken right away on the later the fact that it is logically within human control/ability, unlike climate.